Pelatihan dan Pendampingan Pemasaran UMKM Rengginang Singkong Berbasis Artificial Intelligence di Desa Banasare - Hasanur Mohammad Firdausi; Moh Taufik; Achmad Faqih; Imam Anas Mubarok; Siti Sa’Adah; Nurul Hidayat; Bambang Sri Kaloko; Gamma Aditya Rahardi; Dani Hari Tunggal Prasetiyo (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2026)
This community service program aims to improve the marketing performance of a cassava rengginang micro, small, and medium enterprise (MSME) located in Banasare Village, Rubaru District, which faces limitations in digital marketing capabilities and has not yet utilized artificial intelligence (AI) technology. The partner MSME relies on conventional marketing methods, resulting in limited market reach and low promotional effectiveness. The method employed in this program integrates structured training with hands-on assistance in the implementation of artificial intelligence for marketing purposes. The stages include partner needs analysis through observation and interviews, AI-based marketing training focusing on content creation, direct assistance in applying AI to digital marketing and customer services, and evaluation through a comparison of conditions before and after the program. The results indicate a significant improvement in the partner’s capacity to utilize AI for marketing activities. After participating in the program, the MSME was able to independently create structured digital promotional content using AI tools and implement simple chatbot-based customer service. These changes contributed to more effective promotion, improved service efficiency, and broader market reach compared to the initial condition. The outputs of this community service activity include increased digital marketing skills of the partner MSME, the adoption of AI-based marketing practices, and the development of a replicable training and assistance model suitable for traditional food MSMEs in rural areas. This program demonstrates that artificial intelligence can be applied in a simple and practical manner to support the digital transformation and competitiveness of rural MSMEs.